Sensory function and dependence in older adults with chronic disease - Duran-Badillo, Tirso (Universidad de Sonora, 2020)
Introduction: With aging there are changes in the senses and consequently, alterations in the function of taste and smell that influence the decompensation of chronic diseases. Objective: Know the sensory function and its association with dependence to perform basic and instrumental daily life activities in older adults with chronic diseases. Methodology: Correlational study in a sample comprised by 96 participants. The Instruments used were: Snellen Letter, Manual Hearing meter, Semmes-Weinstein monofilament, flavor test, Basic Tastes, and Barthel Index. The statistic analysis implied the use of descriptive and inferential statistics, Spearman Correlation, and Mann-Whitney U Test. Results: Seventy one percent had visual impairment; 48% got normal hearing in the left ear and 43% in the right ear; 24% rated with tactile alteration in the left foot and 30% with tactile alteration in the right foot; 77% presented alteration of smell and taste. Forty percent had dependence on Basic Activities (ABVD by its acronym in Spanish) and 24% in Instrumental Activities (AIVD by its acronym in Spanish). The relationship between touch in both feet and auditory acuity was identified with ABVD(p=<.05). Age and AIVD(p=<.001), sharp touch in the left foot(p =<.031), auditory(p=<.005),smell(p=<.018),and taste(p=<.047). The dependence on ABVD had no difference in the test with eyeglasses (U-146,000; p-754) and without eyeglasses(U-127,500;p-079); AIVD with eyeglasses(U-115,000;p-079) and without eyeglasses(U-160,000;p-202). Conclusions: The greater the function in the touch and hearing senses, the less the dependence to perform ABVDs and the greater the functions in the touch, hearing, and smell senses, the less the dependence on AIVDs.